2023
DOI: 10.1021/jasms.2c00339
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Location of the α-Synuclein Dimer Interface Using Native Top-Down Fragmentation and Isotope Depletion-Mass Spectrometry

Abstract: α-Synuclein (αSyn), a 140-residue intrinsically disordered protein, comprises the primary proteinaceous component of pathology-associated Lewy body inclusions in Parkinson's disease (PD). Due to its association with PD, αSyn is studied extensively; however, the endogenous structure and physiological roles of this protein are yet to be fully understood. Here, ion mobility-mass spectrometry and native top-down electron capture dissociation fragmentation have been used to elucidate the structural properties assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(106 reference statements)
0
4
0
Order By: Relevance
“…With growing interest and application of CIU, stability shift analyses can become less intuitive depending on the system being studied. For instance, some charge states of α-synuclein have been observed to exhibit parallel CIU features across multiple collision voltages, complicating robust stability comparisons . In addition, CIU of nucleic acids, especially RNAs, typically undergo slight compaction transitions prior to unfolding during CIU, necessitating nonstandard approaches for the evaluation of CIU50 values .…”
Section: Resultsmentioning
confidence: 80%
“…With growing interest and application of CIU, stability shift analyses can become less intuitive depending on the system being studied. For instance, some charge states of α-synuclein have been observed to exhibit parallel CIU features across multiple collision voltages, complicating robust stability comparisons . In addition, CIU of nucleic acids, especially RNAs, typically undergo slight compaction transitions prior to unfolding during CIU, necessitating nonstandard approaches for the evaluation of CIU50 values .…”
Section: Resultsmentioning
confidence: 80%
“…Prior work has demonstrated that CIU can uncover partially folded conformational intermediates that are unique to isoforms and structural states that are overlooked by other MS methods . For instance, CIU has been used to capture subtle differences in protein structure due to disease-associated sequence variation, disulfide bonding, post-translational modifications, and ligand binding . More recently, CIU has been used as a tool to quantify large (66–150 kDa) proteins exhibiting similar molecular weights and sequences. , Despite the ability of CIU to differentiate and quantify subtly different protein variants, CIU has yet to be used to quantify disease-associated small (<15 kDa) biomarkers present in biological matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has demonstrated that CIU can uncover partially folded conformational intermediates which are unique to isoforms and structural states that are overlooked by other MS methods. 61 For instance, CIU has been used to capture subtle differences in protein structure due to disease-associated sequence variation, [62][63][64] disulfide bonding, 65 posttranslational modifications, 66 and ligand binding. 67 More recently, CIU has been used as a tool to quantify large (66-150 kDa) proteins exhibiting similar molecular weights and sequences.…”
Section: Introductionmentioning
confidence: 99%